Studi Perbandingan Pendapatan Usaha Lobster Di Pulau Banyak dan Pulo Aceh - Endri Syahputra; Teuku Muhammad Haja Almuqarramah; Agus Naufal; Suraiya Nazlia (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Pulau Banyak and Pulo Aceh have quite promising potential in the field of fisheries, especially lobster cultivation. In every fishery business activity, the thing that cannot be separated is the process of income analysis. This research was carried out in Ujong Gle Village, Pulo Aceh District, Aceh Besar District and Pulau Bagak Village, Pulau Banyak District. The purpose of this study was to determine the income of lobster business in Pulau Banyak and Pulo Aceh as well as marketing channels. The cost analysis used is fixed cost analysis, variable cost analysis, income analysis and profit analysis. The research method used is a case study. The results showed that the total income earned by lobster entrepreneurs was Rp. 79.150.000. The monthly income of lobster entrepreneurs in Pulau Banyak is Rp. 19,787,500 and Pulo Aceh is Rp. 39,083,300, marketing channels in Pulau Banyak are Medan - Jakarta and Pulo Aceh - Jakarta. The percentage change in lobster prices in Pulau Banyak occurs at the level of bench toke to exporters, the highest percentage change in prices found in sand lobster, which reaches 800%.